Hypertension specific patient-reported outcome measure. Part III: validation, responsiveness and reliability assessment - M. V. Ionov; N. E. Zvartau; E. A. Dubinina; N. N. Khromov-Borisov; I. A. Tregubenko; A. O. Konradi (Российский кардиологический журнал)
Aim. Health-related quality of life in patients with arterial hypertension (HTN) is still determined by only generic patient-reported outcome measures (PROMs), although disease-specific ones are more reliable and highly valid. Previously, we reported the results of development and item-selection process of the new Russian HTN-specific PROM. The purpose of this last stage was to confirm validity, reliability, responsiveness and sensitivity of the scale and to present its final version.Material and methods. Analysis was done using data from a mass survey of patients with Grades 1-3 HTN (n=359, aged 25 to 91 y. o.) and healthy volunteers (n=48, aged 23 to 65 y.o), 407 returned questionnaires. We conducted two exploratory factor analyses (EFA) with the intermediate version of the PROM (80 questions, 20 of them HTN-specific). The Cattel’s scree test was used to select the optimal number of factors. After removing the items with a low factor loadings, a confirmatory factor analysis (CFA) was performed to assess the model’s fitindexes adequacy. The core indexes to be measured were SRMR, RMSEA, CFI. Finally, the PROM’s reliability (Cronbach’s α and McDonald’s ω) and criterion validity (responsiveness) were evaluated.Results. Both EFA with oblique and varimax rotation showed 35 questions have factor loadings ≥0,5 and assigned to one of 5 factors. The basic structure of the PROM was retained for further CFA. Most of indices of fit measured met the requirements: SRMR was 0,08, RMSEA was 0,07 (90% CI (0,07-0,08)) and CFI was 0,08, which confirms the construct validity. Both Cronbach’s α and MacDonald’s ω of each of the domains were ≥0,80 and the whole scale was 0,89 confirming satisfactory reliability. Scores of the questionnaire were positively correlated with the severity of HTN (p<0,001 for Grades 1-3 HTN) and between HTN and non-HTN patients (p=0,01 and 0,04 in psychologic and social domains respectively).Conclusion. Sequentially addressing of exploratory and confirmatory factor analyses and assessment of reliability and responsiveness allowed to form the final version of the patient-reported outcome measure for arterial hypertension. The new Russian-language questionnaire is a useful and feasible tool for routine practice and clinical trials.